(untitled) (Modern education and development, 2025)
This study examines the practical value of translating belles-lettres and publicist texts, focusing on lexico-grammatical transformations as a key methodological tool. The research highlights the complexities inherent in translating academic and literary works, emphasizing the need for meticulous analysis of external (extra-linguistic) and internal (linguistic) textual features. By investigating the semantic and functional roles of lexical and grammatical transformations, the study identifies their critical impact on preserving meaning and stylistic nuances across languages, particularly between Uzbek and English. The paper explores challenges specific to *belles-lettres* (e.g., aesthetic and stylistic individuality) and publicist texts (e.g., emotionality and persuasive function), offering strategies to address functional, conceptual, and socio-cultural translation problems. Examples from literary and political texts illustrate how transformations like compensation or adaptation can mitigate distortions in meaning. The study underscores the absence of a unified theory of translation transformations and proposes a functional classification to guide translators in selecting contextually appropriate techniques.